2017
DOI: 10.1038/srep44091
|View full text |Cite
|
Sign up to set email alerts
|

Tool use for corpse cleaning in chimpanzees

Abstract: For the first time, chimpanzees have been observed using tools to clean the corpse of a deceased group member. A female chimpanzee sat down at the dead body of a young male, selected a firm stem of grass, and started to intently remove debris from his teeth. This report contributes novel behaviour to the chimpanzee’s ethogram, and highlights how crucial information for reconstructing the evolutionary origins of human mortuary practices may be missed by refraining from developing adequate observation techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Interactions may also include objects which are employed in different contexts. One report described a chimpanzee engaging in ‘corpse cleaning’, and suggested that this was both a socially meaningful way of handling the corpse and an attempt to learn about its state (van Leeuwen, Cronin & Haun, ; see also ‘investigatory probing’ in McGrew, , p. 124). After the death of a female lowland gorilla, King () describes the male placing celery (her favourite food) on her hands.…”
Section: Primate Thanatology: Contemporary Reportsmentioning
confidence: 99%
“…Interactions may also include objects which are employed in different contexts. One report described a chimpanzee engaging in ‘corpse cleaning’, and suggested that this was both a socially meaningful way of handling the corpse and an attempt to learn about its state (van Leeuwen, Cronin & Haun, ; see also ‘investigatory probing’ in McGrew, , p. 124). After the death of a female lowland gorilla, King () describes the male placing celery (her favourite food) on her hands.…”
Section: Primate Thanatology: Contemporary Reportsmentioning
confidence: 99%
“…Studies of the ways in which sanctuary-housed primates, primarily chimpanzees, make decisions and solve problems have yielded numerous publications over the previous two decades. Cognitive development [41,125,146,151,152], decision-making [153][154][155][156][157] and tool-use [94,[158][159][160][161][162][163] are some of the most commonly studied topics involving great apes. However, researchers have also investigated several more specific topics with sanctuary-housed chimpanzees, such as the influence of both social presence [164] and early rearing history [165] on problem-solving.…”
Section: (B) Cognitionmentioning
confidence: 99%
“…Therefore, there is a great deal of behavioural complexity surrounding the Neanderthal treatment of the dead in both time and space. At the time of writing, the only other species that seems to have an equally diverse range of motivations and post‐mortem treatment of human bodies is our own (but see van Leeuwen et al ., for an example of chimpanzee practice).…”
Section: Updating Neanderthal Behaviourmentioning
confidence: 99%